O uso das tecnologias da informação e comunicação no processo de ensino e aprendizagem na Faculdade de Medicina da Universidade Federal De Alagoas - Gomes , Weidila Siqueira de Miranda (2016)
This scholarly work of completion-TACC, consisting of a scientific paper and a product of intervention discusses how teachers of medical school of the Federal University of Alagoas using information and communication technologies in the teaching learning process. The method used was a case study, exploratory, descriptive and qualitative, with the participation of 22 teachers, using an electronic questionnaire containing semi-structured questions 17, five being closed for the characterization of teachers and 11 open on ICT in the teaching-learning process in your teaching practice. Most of the teachers interviewed had trained to use ICT and the most used are: blog, chat, e-mail, Skype, portfolio, Word and PowerPoint. For these teachers, ICT were of extreme importance to pedagogical practices and are part of everyday life, helping and contributing to the teaching process learning in teaching practice. It was concluded that the technologies are included in the daily practice of the professors of the Faculty of Medicine of the Federal University of Alagoas and are understood as pedagogical tools of great importance to the teaching learning process, being necessary continuing education policies and update training of technologies not yet used by this academic group, but which are efficient in the construction of scientific knowledge. Through the results obtained has created an educational blog (http://tecnologiasdigitaisnaeducacaoemsaude.blogspot.com.br/), as a product of intervention, to publicize technological tools involved in the teaching learning process, with the purpose of targeting teachers, students, educational managers, educators, professionals of any field to adopt digital technologies in their daily practices.